2014
DOI: 10.1055/s-0033-1358673
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wearing a Ski Helmet on Perception and Localization of Sounds

Abstract: Helmet use on ski slopes has steadily increased worldwide over the past years. A common reason reported for helmet non-use, however, is impaired hearing. Therefore, an intra-subject design study was conducted to compare hearing thresholds and sound source localization of 21 adults with normal hearing in an anechoic chamber when wearing a ski helmet and ski goggles or wearing a ski cap and ski goggles to the condition head bare. Hearing thresholds while wearing a ski helmet (6.8 ± 1.6 dB HL) and ski cap (5.5 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…With regard to these three issues and beside the subjective attitudes of the individuals, there are some evidence-based results from recent studies. Tudor et al [16] and Ruedl et al [17] found that compared to a ski cap a ski helmet showed an increased hearing threshold. However, according to Ruedl et al [17] the degree of the hearing impairment when using a ski helmet is less than what is termed as a hearing impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to these three issues and beside the subjective attitudes of the individuals, there are some evidence-based results from recent studies. Tudor et al [16] and Ruedl et al [17] found that compared to a ski cap a ski helmet showed an increased hearing threshold. However, according to Ruedl et al [17] the degree of the hearing impairment when using a ski helmet is less than what is termed as a hearing impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Tudor et al [16] and Ruedl et al [17] found that compared to a ski cap a ski helmet showed an increased hearing threshold. However, according to Ruedl et al [17] the degree of the hearing impairment when using a ski helmet is less than what is termed as a hearing impairment. In addition, as most injuries on ski slopes occurred after a self-inflicted fall without involvement of another skier or snowboarder [2,15,18], compared to an impaired hearing an impairment of vision might be a more essential factor for safety in alpine skiing.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects responded verbally by naming the number of the loudspeaker where they perceived the sound to come from. Numbers of loudspeakers corresponded to the digits of a clock face, with “12” indicating the front position and “6” indicating the rear position [ 8 , 9 , 15 ] (Ruedl et al, 2014; Seebacher et al, 2015; Ruedl et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…A major reason for this may be its adverse effect on sound perception [ 6 ] (Ruedl et al, 2012). Evidence shows that wearing a ski helmet significantly worsens hearing thresholds as well as sound source localization in comparison to bare head, and partially even in comparison to wearing a cap [ 7 , 8 , 9 ] (Tudor et al, 2010, Ruedl et al, 2014, Ruedl et al, 2019). Although the worsening of the hearing thresholds is not much (<20 dB) and is limited to the high frequency region, it may nevertheless have a detrimental impact on a skier’s ability to identify correctly the sound source direction of perceived sounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation